Dynamics of Capsaicin Content of Red Chili (Capsicum annum L.) under Various Nutrient and Fertilization Statuses - Okto Prandi Sihombing; Sarifuddin; Mariani Sembiring (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Accurate fertilization is an important factor affecting plant productivity. Indonesia currently ranks fourth amongthe world's largest red chili producers, but its productivity remains relatively low. Efforts to increase productivitycan be achieved through soil and plant analysis to provide site-specific fertilizer recommendations tailored toplant needs. This study aims to develop site-specific fertilizer recommendations to increase red chili productivityand to analyze the relationship between plant nutrient status and capsaicin content in Lubuk Cuik Village, LimaPuluh Pesisir District, Batubara Regency. The study was conducted at an altitude of 8 m above sea level using asurvey method. Plant samples were selected purposively based on differences in variety and harvest time, thenanalyzed in the laboratory as a basis for compiling fertilizer recommendations. The results showed that thenutrient status of red chili plants at the study site remained below optimal levels. Therefore, site-specificfertilizer recommendations were developed using a combination of three approaches: maintenance, sufficiency,and build. The fertilization guidelines were designed to achieve a yield of 21 tons/ha for the following varieties:Jitu (Urea 531 kg/ha, TSP 92 kg/ha, KCl 258 kg/ha), Laju (Urea 505 kg/ha, TSP 96 kg/ha, KCl 258 kg/ha), andlocal variety (Urea 513 kg/ha, TSP 94 kg/ha, KCl 255 kg/ha), assuming that crop residues are returned to thefield. Multiple regression analysis indicated that the relationship between nutrient status and capsaicin contentwas not statistically significant (R² = 0.084). However, nitrogen (N) and sulfur (S) tended to increase capsaicinlevels, whereas potassium (K) and phosphorus (P) tended to decrease them. The novelty of this study lies in thesimultaneous use of three approaches to link plant nutrient status analysis with site-specific fertilizerrecommendations, which is relatively new in red chili research.